Polymorphisms in glutathione-related genes modify mercury concentrations and antioxidant status in subjects environmentally exposed to methylmercury - Barcelos, Gustavo Rafael Mazzaron; Grotto, Denise; de Marco, Kátia Cristina; Valentini, Juliana; Lengert, André van Helvoort; Oliveira, Andréia Ávila Soares de; Garcia, Solange Cristina; Braga, Gilberto Úbida Leite; Schläwicke Engström, Karin; Cólus, Ilce Mara de Syllos; Broberg, Karin; Barbosa, Fernando (The Science of the total environment, 2013)
Methylmercury (MeHg) toxicity may vary widely despite similar levels of exposure. This is hypothetically related to genetic differences in enzymes metabolizing MeHg. MeHg causes oxidative stress in experimental models but little is known about its effects on humans. The aims of the present study was to evaluate the effects of polymorphisms in glutathione (GSH)-related genes (GSTM1, GSTT1, GSTP1 and GCLM) on Hg concentrations in blood and hair, as well as MeHg-related effects on catalase (CAT) and glutathione-peroxidase (GPx) activity and GSH concentrations. Study subjects were from an Amazonian population in Brazil chronically exposed to MeHg from fish. Hg in blood and hair were determined by ICP-MS, CAT, GPx and GSH were determined by spectrophotometry, and multiplex PCR (GSTM1 and GSTT1) and TaqMan assays (GSTP1 and GCLM) were used for genotyping. Mean Hg concentrations in blood and hair were 48±36μg/L and 14±10μg/g. Persons with the GCLM-588 TT genotype had lower blood and hair Hg than did C-allele carriers (linear regression for Hg in blood β=−0.32, p=0.017; and hair β=−0.33; p=0.0090; adjusted for fish intake, age and gender). GSTM1*0 homozygous had higher blood (β=0.20; p=0.017) and hair Hg (hair β=0.20; p=0.013). Exposure to MeHg altered antioxidant status (CAT: β=−0.086; GSH: β=−0.12; GPx: β=−0.16; all p<0.010; adjusted for gender, age and smoking). Persons with GSTM1*0 had higher CAT activity in the blood than those with GSTM1. Our data thus indicate that some GSH-related polymorphisms, such as GSTM1 and GCLM may modify MeHg metabolism and Hg-related antioxidant effects. •Study subjects are highly exposed to methylmercury via fish intake.•Exposure to methylmercury leads to disturbances of antioxidant status.•Polymorphisms of GSH-related genes may modulate mercury bodyburden.•Genetic effects were seen also on parameters of antioxidant status.